2008
DOI: 10.1002/mawe.200700216
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface residual stresses on gigacycle fatigue response of high chromium cold work tool steel

Abstract: The effect of surface compressive residual stresses (RS) induced by surface grinding and polishing on the gigacycle fatigue behavior of medium-carbon high-chromium alloy cold work tool steel was evaluated. Two test series were performed: Specimens of series I revealed high compressive RS of about -800 MPa at the surface, resulting from grinding with fine emery paper, which treatment had definitely a beneficial influence on the fatigue endurance strength. The existence of surface RS was also revealed to be resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 25 publications
(30 reference statements)
2
27
0
Order By: Relevance
“…This is confirmed by other authors as well. [13][14][15][16][17][18][19][20][21][22][23][24][25][26]38] As a result, the fatigue strength can scatter strongly since the heterogeneous carbide microstructures in ingot cast and hot worked tool steels show strong deviation of carbide sizes comparing rolling and transverse directions. [12] Beiss, [11] Sohar et al, [16] and Randelius et al [25,26] confirmed this anisotropy effect and specify that smaller carbides are found in rolling directions of ingot cast and hot worked materials, thus up to 60% higher fatigue strength can be achieved.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is confirmed by other authors as well. [13][14][15][16][17][18][19][20][21][22][23][24][25][26]38] As a result, the fatigue strength can scatter strongly since the heterogeneous carbide microstructures in ingot cast and hot worked tool steels show strong deviation of carbide sizes comparing rolling and transverse directions. [12] Beiss, [11] Sohar et al, [16] and Randelius et al [25,26] confirmed this anisotropy effect and specify that smaller carbides are found in rolling directions of ingot cast and hot worked materials, thus up to 60% higher fatigue strength can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…[12,25,26] In addition, surface conditions and treatments can affect the fatigue performance of tool steels, e.g., different hard machining and polishing processes or surface treatments and finishing techniques. [17,20,26,[33][34][35][36][37] Sohar et al [13][14][15][16][17][18][19][20] focused on the effects of manufacturing, carbide microstructure and compressive residual stresses (CRS) on the UHCF strength and failure mechanisms. They separate three different failure modes for ingot cast tool steels depending on the present residual stresses at the specimen surface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some investigators like [1,2,3] have shown, that compressive residual stresses at the surface of specimens due to local plastic deformation or local plastic deformation and reduction of surface roughness, increases the lifetime also in the very high cycle regime. From these results it is known, that the compressive mean stress inhibits the crack initiation at or close to the surface, until the influence is compensated by crack initiation in the volume of the specimen.…”
Section: Introductionmentioning
confidence: 99%